(untitled) (Shanti Journal, 2023)
From literature to digital media, through numerous misleading interpretations, the patriarchal society has quite successfully made the female body an object of control and gaze. The reflection of these oppressions can be found in Arupa Patangia Kalita’s short stories. The paper has intended to read the representation of the female body in selected short stories of Kalita namely ‘The Girl with Long Hair,’ ‘Ayengla of the Blue Hills,’ ‘Kunu’s Mother,’ and ‘The Call Girls at the Shelter Home.’ As all the selected short stories have been written of women, for women, and by a woman, the paper has tried to examine whether Kalita’s narratives can be called the specimen of ‘Écriture Féminine’ or not. The paper has mainly adopted textual analysis method to analyse the primary and secondary sources. By analysing the secondary sources various characteristics of the philosophy ‘Écriture Féminine’ have been found. The stories then have been analysed in respect to these themes to come to the conclusion that they bear synonymity with the said philosophy.